Dual pulse heterodyne distributed acoustic sensor system employing SOA-based fiber ring laser - Zhang, Chunxi; Yang, Sufan; Wang, Xiaxiao (Frontiers in Physics, 2023)
In this paper, a dual-pulse heterodyne distributed acoustic sensor (DAS) system using a semiconductor optical amplifier (SOA)-based fiber ring laser (FRL) is demonstrated theoretically and experimentally. The physical mechanism of the SOA is theoretically investigated, and a simple theoretical model of the SOA-based FRL is presented. The adaptability of the SOA-based FRL in the DAS system has been demonstrated in the experiments. Unlike the previous DAS system configurations, the SOA-based FRL replaces the narrow linewidth laser (NLL) and pulse modulator, reducing costs and simplifying the system. Using the dual-pulse heterodyne detection method, the sensor system responds well to distributed acoustic sound detection and achieves accurate demodulation and positioning. A high signal-to-noise ratio(SNR) of 42.51 dB at 3 kHz is demonstrated as a demodulation result. The system’s frequency range is 5 Hz to 5 kHz with a spatial resolution of 12 m. The proposed approach shows a broad application prospect for low-cost, large-scale, high-SNR distributed acoustic detection in maritime surveillance.